Optimalisasi Produksi Alat Gali-Muat dan Alat Angkut dengan Metode Quality Control Circle (QCC) Pada Proses Penambangan Batukapur Di Area Existing PT. Semen Padang - Andre Rahmat Saputra; Yoszi Mingsi Anaperta; Riko Maiyudi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstrack Based on the production data limestone minning at existing area of PT. Semen Padang in January-February 2018, limestone mining production did not reach the target. This is due to the low productivity of the dumptruck. To find out the improvement potential of a production process and the effectiveness of using equipment, it is necessary to do an analysis using the Quality Control Circle (QCC) method. After knowing the root of the problem, ideas for improvement are given to obstacles so that production can be achieved. After doing the analysis and improvement with these methods, the production of the komatsu HD 785-7 dumptruck exceeded the planned target. However, for the values of PA, MA, UA and EU, each conveyance is still < 85% has not yet reached the optimal world class value that is > 85%, it can be concluded that the condition of the equipment is not good. It is better to do repairs to standby time and tool breakdown. Keywords: Production, Quality Control Circle, Pareto Diagram, Fishbone Method, komatsu hd 785-7 dumptruck